Operational benefits of autonomous vessels in logistics—A case of autonomous water-taxis in Bergen. (October 2021) - Gu, Yewen; Wallace, Stein W.
Abstract: Although the technology of autonomous vessels has developed rapidly in the past decade, the literature on the effects of this new technology on logistics and transportation is limited. Particularly, the potential operational changes brought by the autonomy of vessels are not discussed. Besides savings on crew, other benefits of autonomy, especially from an operational perspective, remain unclear. On the other hand, countries like Norway are facing significant challenges in their urban and rural logistics. The land-based public transportation system cannot efficiently serve the demands, especially for areas isolated or separated by fjords or rivers. Water-based transportation systems are thus very attractive, and autonomy makes such systems economically more viable. In this paper we focus on a potential case of autonomous water-taxis in Bergen, Norway. First, we identify the major operational differences, from a logistics perspective, between conventional manned water-taxis and autonomous ones. Then a mixed integer linear programming model is developed to tackle the facility location, fleet allocation and routing decisions in the daily operations of a water-taxi business. The model in this paper is used to analyse the problem, rather than designed for direct use during implementation. In the computational study, different cases with either conventional or autonomous water-taxis are tested. The results show that autonomy can lead to substantial savings on travelled distance due to number and locations of parking terminals being feasible only for autonomous systems. Highlights: Autonomous vessels bring operational advantages apart from lower variable costs. A MILP model is developed to explore the operational benefit of autonomous vessels. A case of autonomous water-taxis in Bergen is used for a computational study. New depot locations and route choices lead to shorter travelling distance.